Efektivitas Metode Index Card Match pada Penerapan Pembelajaran Ilmu Tajwid Kelas IV di SDN Lagadar 01 - eva samantha pertiwi; Nan Rahminawati; Fitroh Hayati (UNISBA Press, 2024)
Abstract. The lack of effectiveness of student learning outcomes is the result of many things, one of which is the inappropriate use of learning methods. Therefore, it is hoped that the application of the index card match method can answer problems and increase the effectiveness of student learning outcomes. This research aims to find out how much the effectiveness of student learning outcomes has increased. This research was conducted on the Qur'an subject, Tajwid science material. This research was conducted in class IV B at SDN Lagadar 01 using a quantitative approach and quasi-experimental methods. Data collection techniques use interviews, tests and observations. Data analysis used the normality test, homogeneity test, and independent samples t test.The results of the research showed that the experimental class which used the index card match method was superior in the level of effectiveness of student learning outcomes to the control class which used conventional methods in Al Qur'an Subjects, Tajwid Science material. This can be seen from the average learning value after implementing the index card match method. The results of research on the learning process of the experimental class and control class show that the value of the control class is greater. Next, data analysis was carried out through an independent samples t test with the help of SPSS, the results were that there were significant differences in learning outcomes between the experimental class which used the index card match method and the control class which used the conventional method. This shows that the Index Card Match method is more effective when applied to learning the Qur'an, Tajwid Science. Abstrak. Kurangnya efektifitas hasil belajar siswa merupakan akibat banyak hal, salah satunya kurang tepatnya penggunaan metode belajar. maka dari itu, penerapan metode index card match diharapkan dapat menjawab permasalahan serta meningkatkan efektivitas hasil belajar siswa. Penelitian ini bertujuan untuk mengetahui seberapa besar peningkatan efektivitas hasil belajar siswa. Penelitian ini dilakukan pada Mata Pelajaran Al Qur’an materi Ilmu Tajwid. Penelitian ini dilakukan di kelas IV B SDN Lagadar 01 dengan menggunakan pendekatan kuantitatif dan metode quasi eksperimen. Teknik pengumpulan data menggunakan wawancara, tes dan observasi. Analisis data menggunakan uji normalitas, uji homogenitas, dan uji independent samples t test. Hasil penelitian menunujukkan bahwa kelas eksperimen yang menggunakan metode index card match lebih unggul tingkat efektivitas hasil belajar siswa dari kelas kontrol yang menggunakan metode konvensional pada Mata Pelajaran Al Qur’an materi Ilmu Tajwid. Hal ini terlihat dari nilai rata-rata belajar sesudah pelaksanaan metode index card match. Hasil penelitiaan terhadap proses belajar kelas eksperimen dan kelas kontrol menunjukkan bahwa kelas kontrol lebih besar nilainya. Selanjutnya dilakukan analisis data melalui uji independent samples t test dengan bantuan SPSS, hasilnya terdapat perbedaan signifikan hasil belajar antar kelas eksperimen yang menggunakan metode index card match dengan kelas kontrol yang menggunakan metode konvensional. Hal itu menunjukkan bahwa metode Index Card Match lebih efektif untuk diterapkan pada pembelajaran Al Qur’an Ilmu Tajwid.